Pertanggungjawaban Pidana terhadap Pelaku Penyebaran Data Pribadi di Media Sosial dalam Perspektif Undang-Undang Pelindungan Data Pribadi - Masroor Ahmad Alam (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
concerning form of misuse is the dissemination of another person’s personal data without consent, including full names, home addresses, phone numbers, photographs, family identities, employment information, financial data, and screenshots of private conversations. This article aims to analyze the criminal regulation of perpetrators who disseminate personal data on social media and to formulate a proportional model of criminal liability from the perspective of Law Number 27 of 2022 concerning Personal Data Protection. This study applies normative juridical research using statutory, conceptual, and case approaches. The primary legal materials include the Personal Data Protection Law, the Electronic Information and Transactions Law and its amendments, the national Criminal Code, the Criminal Adjustment Law, and Constitutional Court decisions concerning the review of the Personal Data Protection Law. The findings show that disseminating personal data on social media may qualify as unlawful disclosure or use of personal data belonging to another person. Criminal liability requires the fulfillment of legal subject, criminal act, unlawfulness, intent, capacity for responsibility, and the relevance of harm or potential harm suffered by the data subject. The Personal Data Protection Law provides a more specific basis for criminalization; however, its enforcement must consider proportionality, legitimate public interest, freedom of expression, and victim protection.